Biodiversity surrogates in Amazonian iron cave ecosystems. (June 2019) - Trevelin, Leonardo C.; Gastauer, Markus; Prous, Xavier; Nicácio, Gilberto; Zampaulo, Robson; Brandi, Iuri; Oliveira, Guilherme; Siqueira, José O.; Jaffé, Rodolfo
Highlights: Tropical caves harbor many endemic and often threatened species. Here we identify biodiversity surrogates for obligate subterranean dwellers. Patterns of community concordance with phylogenetic distinctiveness were assessed. Surrogates were robust to sampling biases, spatial scale and ecological gradients. Surrogates could assist monitoring programs and iron cave conservation efforts. Abstract: An approach to deal with biodiversity knowledge shortfalls in conservation is to base systematic planning and monitoring on surrogate taxa that represent diversity patterns of the whole studied system. By adopting evolutionary history to guide the search for these suitable surrogates, it is possible to use lineage differences as predictors of biological processes promoting overall diversity. Tropical cave ecosystems are among the least known terrestrial ecosystems, and yet harbour a diverse array of organisms, among which obligate subterranean dwellers (troglobites) stand out as primary targets for conservation. In the present study, we take advantage of a bio-speleological database of iron caves located in south-eastern Amazonia to examine regional patterns of community concordance among the taxonomic and ecological grouping of troglobitic species. Relying on species incidence data and a phylogenetic classification of these species, we estimate the evolutionary distinctiveness weighted by the extinction risk for each of them and relate this measure to community composition, identifying the best taxonomic surrogates of troglobite diversity. We evaluated similarity patterns of community composition based on a Procruste's methodological approach, and then tested the resulting concordance patterns for scale and sampling biases. We also evaluated selected concordance results across spatial and environmental gradients, using a distance-based redundancy analysis. Our results reveal that the ordination of rare species was poorly correlated to the ordination of the evolutionary classification of species, whereas Entognatha and Arachnida together presented high values of concordance. Furthermore, the concordance patterns we depict scale up to the geomorphological features that characterize the region, suggesting their importance in shaping biodiversity patterns in this system. Our findings have important conservation implications, as they show that the current focus on rare species does not guarantee the conservation of evolutionary uniqueness in iron cave ecosystems.